Hitch suture assisted tuck in Tenon's Patch Graft for management of Corneal Perforations. Issue 6 (November 2022) - Bafna, Rahul Kumar; Kalra, Nidhi; Rathod, Aishwarya; Asif, Mohamed Ibrahime; Lata, Suman; Parmanand, Kumar; Kaur, Navpreet; Kittur, Amogh Shreekant; Shakkarwal, Chetan; Roop, Prakhyat; Agarwal, Rinky; Agarwal, Tushar; et al.
Purpose: To describe a novel modification of tuck-in Tenon's patch graft (TPG) using temporary horizontal mattress sutures and fibrin glue to hitch the graft in the management of corneal perforations. Design: Ambispective interventional case series. Methods: Modified technique of autologous TPG was used to seal corneal perforations measuring 3–5 mm, using horizontal mattress sutures to hitch the graft in a lamellar pocket, followed by application of fibrin glue. The horizontal mattress sutures were removed after the reformation of the anterior chamber. The primary outcome measure was a well formed anterior chamber in the post-operative period and the secondary outcome was epithelization time. Results: The surgery was performed in 22 eyes. The mean age was 43.86 ± 16.02 (26–66) years, with 14 males and eight females. The etiologies of corneal perforation included dry eye (n = 10), neurotrophic keratitis (n = 6), trauma (n = 2), chemical injury (n = 2) and exposure (n = 2). The mean size of the perforation with the thinned-out area was 4.3 mm (range 3–5 mm). The mean duration of epithelialization was 14.31 ± 2.63 days (7–21 days). No intraoperative complications were observed. All eyes had a well-formed anterior chamber in the immediate postoperative period. Postoperatively, two eyes had graft pseudoectasia due to a thick graft and supra tenon haemorrhage each; one eye each had graft thinning with the formation of pseudopterygium and graft melting. Conclusion: Tenon's patch graft, along with the use of temporary horizontal mattress sutures and fibrin glue, is an effective modification of the technique for managing corneal perforations measuring 3–5 mm.